“DESIGN AND DEVELOPMENT OF 2D ANIMATION ABOUT THE DANGERS OF CONSUMING INSTANT NOODLES IN EXCESS BY USING FRAME BY FRAME AND TWEENING TECHNIQUES ” - Heru Wijayanto Aripradono; Winson Ng (Universitas Internasional Batam, 2022)
A Healthy living is an effort to maintain and improve the health of the body by consuming healthy food and exercise. One attitude to healthy living is to consume a balanced menu. A balanced menu is a daily diet that meets the nutrients needed by the body. As time goes on, the needs of human life increase. Busyness in all activities so that we do not pay attention to basic needs, such as food. From that arise entrepreneurs to produce fast food ingredients such as instant noodles. Instant noodles have become a food that is familiar to the community, especially students. This instant noodle if consumed in excess can cause cholesterol and many more diseases. Therefore, the author uses animated 2D video as a notification medium. The methods in this study use pre-production, production and post-production methods. Using this method will result in a 2D animation, which uses the Toon Boom Harmony application. The results of this implementation are in the form of 2D Animated Videos about the dangers of consuming instant noodles excessively that will be uploaded to the UIB Information System Youtube Channel. It is expected that from this animated video people get social media about the dangers of consuming instant noodles in excess which is more interesting.